The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.21276/aimdr.2018.4.1.og1
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal Obstruction after Excision of a Transverse Vaginal Septum: A Rare Case Report

Abstract: A vaginal obstruction often occurs as a result of complication in women who had previously undergone an excision of a transverse vaginal septum. Her we are reporting a case of 12 years old unmarried girl presented with complaint of secondary amenorrhea and cyclic pain lower abdomen since two months. She was operated for cryptomenorrhea four months back. On examination under anaesthesia Thick scarred septum was present in vaginal canal about 6-7 cm from vaginal introitus .After sharp dissection hematocopos bulg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The use of PAI for implant monitoring has been previously explored in studies such as by Lee et al [59] (Figure 7), who achieved reasonable ability to distinguish titanium implant covered by bone or meat, at depths relevant for dentistry applications. However, the depth penetration limit and noticeable optical attenuation makes it increasingly difficult to image the targets that are located deeper than 10-20 mm, limiting the clinical application of PAI to targets near the surface [60]. At the same time, PAI resolution is dependent on the depth based on "factor of 200 rule of thumb", with resolution being 1/200th of the depth [61,62].…”
Section: Photoacoustic Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of PAI for implant monitoring has been previously explored in studies such as by Lee et al [59] (Figure 7), who achieved reasonable ability to distinguish titanium implant covered by bone or meat, at depths relevant for dentistry applications. However, the depth penetration limit and noticeable optical attenuation makes it increasingly difficult to image the targets that are located deeper than 10-20 mm, limiting the clinical application of PAI to targets near the surface [60]. At the same time, PAI resolution is dependent on the depth based on "factor of 200 rule of thumb", with resolution being 1/200th of the depth [61,62].…”
Section: Photoacoustic Imagingmentioning
confidence: 99%
“…Polymers 2021, 13, x FOR PEER REVIEW 11 of 2 the depth penetration limit and noticeable optical attenuation makes it increasingly diffi cult to image the targets that are located deeper than 10-20 mm, limiting the clinical ap plication of PAI to targets near the surface [60]. At the same time, PAI resolution is de pendent on the depth based on "factor of 200 rule of thumb", with resolution being 1/200th of the depth [61,62].…”
Section: Photoacoustic Imagingmentioning
confidence: 99%
“…Patrick et al demonstrated non-invasive whole brain imaging of tau targeting PBB5 probes using volume multispectral photoacoustic tomography (vMSOT) in a 130 m resolution 4-replicate tau P301L model [24]. PAI combines high optical contrast with high ultrasonic resolution, but its maximum detection depth in breast tissue (about 106.4 mm [25]) remains a limitation for wider applications.…”
Section: Introductionmentioning
confidence: 99%